Does opportunity to learn explain the math score gap between madrasah and non-madrasah students in Indonesia? - Ahmad Umar; Kusaeri Kusaeri; Ali Ridho; Ahmad Yusuf; Ahmad Hanif Asyhar (LPMPP Universitas Negeri Yogyakarta, 2022)
The opportunity to learn (OTL) is one of the important aspects of achieving the goal of the learning process. There have been three dimensions of OTL: instructional time (IT), content covered during instruction (CC), and quality of instruction (QI) mentioned in the literature and used as a framework in this article. This study aims to reveal the gap in math ability between madrasah and non-madrasah students in Indonesia and the contribution of the three OTL aspects toward math scores. This study employed a cross-sectional survey approach with self-report instruments. The data were obtained from a survey of participants in the New Students National Selection for Madrasah Aliyah Negeri (Islamic High-school managed by the ministry of religious affairs) in 2021. There were 8,258 participants, consisting of 4,842 students from madrasah and 3,416 from non-madrasah. This study used multilevel structural equation modeling (SEM) to analyze the data. The findings show that (a) there is a gap in math ability score between madrasah and non-madrasah students which is -27, with a mean math ability score of madrasah students being lower than non- madrasah students, and (b) the time invested in learning significantly affects the occurrence of gaps in math ability scores, while the scope of the materials and the quality of learning do not affect the occurrence of the gap in math ability scores. These findings suggest that it is important for the Ministry of Religious Affairs to consider the addition of mathematical lesson duration in madrasah while restructuring the allocation for Islamic lessons.